Mezzanine financing instruments in comparison to the classic financing sources - Tetrevova, Libena; Svedik, Jan (Business, Management and Economics Engineering, 2018)
The paper deals with innovated financing in the form of mezzanine financing instruments (sources). The authors aimed to identify, characterize, and assess mezzanine financing instruments in comparison to the classic corporate financing sources. Mezzanine financing represents an innovated form of financing interconnecting the features of equity and debt. The paper specifies the sources and characterizes and assesses pros and cons of each of them. Subsequently, it presents an overall evaluation of mezzanine financing instruments in comparison to the selected equity and debt financing sources. This evaluation was performed on the basis of 14 set criteria using a binary scale.